Empowering Kauman Community Members in Malang City through Dragon Fruit Peel Cookie Making - Andika, Venny Kurnia; Sawu dan Yushinta Elsa Valina, Sirilus Deodatus; Valina, Yushinta Elsa (Journal of Community Practice and Social Welfare, 2024)
Cookies are calorie-dense snacks made from flour with low dietary fiber content due to the addition of sugar, fat, and eggs, making them less beneficial for health if consumed continuously. Nowadays, there is a need for innovation in providing functional food in the form of healthy and safe cookies for individuals with health issues. Dragon fruit peel is rich in antioxidants and contains high dietary fiber due to its pectin content, along with being a source of several beneficial minerals and vitamins, making it a suitable ingredient for making cookies. This empowerment activity aims to enhance the knowledge of PKK members regarding the production of functional food in the form of dragon fruit peel cookies. The activity consists of 3 (three) stages. The first stage involves an explanation of functional food cookies made from dragon fruit peel, the second stage focuses on the process of making healthy dragon fruit peel cookies, and the third stage entails practical cookie-making using dragon fruit peel. Evaluation is conducted by administering pretests and post-tests. Based on the evaluation results, the pretest score (average=61.16) increased by 53.55% after the post-test (average=93.91). This indicates that the information provided regarding the production of dragon fruit peel cookies was well understood by the participants and suggests the success of the conducted empowerment activity.